2019
DOI: 10.1109/rbme.2018.2886237
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging and Machine Learning for Dementia Diagnosis: Recent Advancements and Future Prospects

Abstract: Dementia, a chronic and progressive cognitive declination of brain function due to disease or impairment, is becoming more prevalent due to the aging population. A major challenge in dementia is achieving the accurate and timely diagnosis. In recent years, neuroimaging with computer-aided algorithms have made remarkable advances in addressing this challenge. Much of the success of these approaches can be attributed to the application of machine learning and deep learning techniques for neuroimaging. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 101 publications
0
62
0
1
Order By: Relevance
“…35 Meanwhile, findings from studies that reported improvement in diagnosis sensitivity and specificity by applying machine learning to the multi-biomarker analysis have been used in real-world cases to classify the cancer-related biomarkers; moreover, machine learning has been applied in cases of in-vitro diagnosis of diseases such as tuberculosis and dementia. 36 37 38 39 …”
Section: Ai Application Areas In Health Carementioning
confidence: 99%
“…35 Meanwhile, findings from studies that reported improvement in diagnosis sensitivity and specificity by applying machine learning to the multi-biomarker analysis have been used in real-world cases to classify the cancer-related biomarkers; moreover, machine learning has been applied in cases of in-vitro diagnosis of diseases such as tuberculosis and dementia. 36 37 38 39 …”
Section: Ai Application Areas In Health Carementioning
confidence: 99%
“…Brain imaging is often used to detect neurological causes (e.g., tumors, stroke), but not psychopathology (Vernooij et al, 2019). In the interpretation of radiological images, AI techniques can outperform specialists in detecting early or "preclinical" degradation of neuroanatomy because AI is particularly well suited to detecting abnormalities within image and signal data through training (i.e., pattern recognition) (Ahmed et al, 2019;Hosny et al, 2018). AI offers the potential to improve interpretability and clinical utility of neuroimaging and neurophysiological data that are commonly obtained but incompletely understood.…”
Section: Neuroimaging and Neurophysiological Data (Table 1 Section C)mentioning
confidence: 99%
“…In academic communities, functional neuroimaging such as functional MRI (fMRI), electroencephalography (EEG), and more recently magnetoencephalography (MEG), are additionally used. The analyses of neuroimaging data are now providing a growing arena for the application of data-driven artificial intelligence (AI) techniques, and more recently, a subclass of AI called machine learning (ML) [46,2,13]. This is in parallel with (forward) model-driven analyses such as the neurobiologically based dynamic causal modeling (see e.g.…”
Section: Data-driven and Ai Approachesmentioning
confidence: 99%